Development of a unified system for assessing health related quality of life across the cancer care continuum: the EUonQoL Delphi study to identify priorities for quality of life domains - Maike G. Sweegers; Esther de Jongh; Christopher Bedding; Emma Nicklin; Daniela Doege; Sara Alfieri; Laura Gangeri; Bianca Scacciati; Augusto Caraceni; Cinzia Brunelli; Anne Bredart; Leslye Rojas-Concha; et al. (Journal of Patient-Reported Outcomes)
Abstract Introduction Cancer and cancer treatment have a major impact on health related quality of life (HRQoL). To improve the assessment of HRQoL in patients with cancer and evaluate the impact of policy interventions, the European Oncology Quality of Life (EUonQoL) project aims at developing a digital, patient centred system to assess HRQoL based on evaluations and preferences of cancer patients and survivors: the EUonQoL-kit. Method Patients across the cancer care continuum, healthcare professionals and researchers from six European countries (Denmark, France, Germany, Italy, The Netherlands and United Kingdom) were asked to rate the importance of 44 pre-selected HRQoL subdomains over a maximum of three Delphi survey rounds. We evaluated the importance of HRQoL subdomains for three target populations: patients undergoing active treatment, cancer survivors and patients receiving palliative care. The results were discussed during a consensus meeting. Results 96 patients and 59 healthcare professionals participated in the Delphi study. After three rounds, consensus was reached for 20 subdomains: ability to work, communication with healthcare professionals, diarrhoea, fatigue, fear of recurrence, global health status, impact of treatment side effects, impact on children/family, insomnia, instrumental activities of daily living, maintaining independence, mobility, nausea, overall quality of life, pain, partner relationship, social activity limitations, social isolation, symptom awareness and uncertain prognosis. The subdomains pain and fear of recurrence were rated as important for all three target populations. Conclusion Subdomains that were considered important for the assessment of HRQoL in patients with cancer can be summarised into: physical symptoms, mobility & activity, future outlook, social roles & activities, family & relationships, social isolation, self-efficacy, overall HRQoL, and healthcare experience. The importance of the subdomains differed for patients in different phases of the cancer care continuum. These findings were used for the creation of the first version of the EUonQoL-Kit, as a base for its further development.